Systematic Analysis on Mobile Botnet Detection Techniques Using Genetic Algorithm - Rahman, MZA; Madihah Mohd Saudi (Springer, 2024)
Nowadays smart phone has been used all over the world and has become as one of the most targeted platforms of mobile botnet to steal confidential information especially related with online banking. It is seen as one of the most dangerous cyber threat. Therefore in this research paper, a systematic analysis on mobile botnet detection techniques is further investigated and evaluated. A case study was carried out to reverse engineering the mobile botnet codes. Based on the findings, this mobile botnet has successfully posed itself as a fake anti-virus and has the capability to steal important data such as username and password from the Android-based devices. Furthermore, this paper also discusses the challenges and the potential research for future work with relate of the genetic algorithm. This research paper can be used as a reference and guidance for further study on mobile botnet detection techniques.